Intrinsic Contribution of Mass Transport within Nanoscale Channels of Nanoporous Gold for CO2 Electrochemical Reduction. Issue 24 (28th July 2022) - Yu, Tianshui; Zhou, Xiangji; Chen, Yu; Chen, Jin; Yuan, Songliu; Qian, Lihua; Lu, Xianglong; Liu, Pan; Lei, Pengxiang; Li, Xiuhong
Abstract: Electrochemical reduction enables the conversion of CO2 into fuel in favor of its global circulation. Nanoporous metals with interconnected and unique skeletons contain large amounts of active sites for effective catalysis, while reaction dynamics are usually stuck by mass transport limited by nanoscale channels. In this work, nanoporous gold (NPG) with different pore sizes is utilized to evaluate the intrinsic behavior of mass transport within nanoscale channels. By defining one comprehensive parameter to exclude the effect of crystalline facets, the intrinsic contribution of mass transport within nanoscale channels to catalytic activity is experimentally identified. Identical correlations between pore size and specific current density are observed in two kinds of NPG that contain crystalline facets with obviously different fractions and comparable fractions. Therefore, the specific current density of CO production monotonously increases with pore size, with a subsequent saturation in both NPG. The critical size of 46 nm correlating with mass transport within nanoscale channels offers one fundamental principle to design hierarchically porous catalysts with high electrochemical activity in the future. Abstract : An effective method is proposed to ascertain the contribution of pore size by using the comprehensive parameter that is contributed by electrochemical surface areas and surface crystal facets. After normalization, an essential correlation between pore size and specific activity is obtained in nanoporous gold.